Risk seeking or averse, how do analyst coverage and firm visits motivate managers? - Hangbo Liu; Xuemeng Guo; Dachen Sheng (PLoS ONE, 2025)
In this research, we use Chinese stock exchange listed firm data to explore the relationship between institutional analysts’ firm visits and firms’ risk-taking as measured by earnings quality. The results show that more frequent visits in the previous year increase managers’ risk-taking decisions in later years and that firms experience lower earnings quality. Interestingly, the concentration of shareholding and management power, traditionally believed to be negative corporate governance instruments, alleviate such risk-taking if a firm is a state-owned enterprise (SOE). For non-SOEs, the more concentrated the shareholding and management power the further the risks increase. These results are attributed to the political connection of the manager, which would make managers more risk averse when under market focus and minimize risks that would damage their reputation and political career.